2012
DOI: 10.1021/jf302054b
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Growth of Cotton Bollworms by Metabolites from an Entomopathogenic Fungus Paecilomyces cateniobliquus

Abstract: Chemical investigation of one entomopathogenic fungus Paecilomyces cateniobliquus YMF1.01799 led to the isolation and identification of six metabolites, which include three new compounds (2-3, and 5) and three known metabolites. Their structures were established by spectroscopic studies such as 1D and 2D NMR and MS analysis. Insect growth experiments suggested that polyketide-derived compound 1 showed significant inhibitory effect on the growth of cotton bollworm Helicoverpa armigera, while terpenoid-derived m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 16 publications
(32 reference statements)
1
21
0
Order By: Relevance
“…Compared to the rice culture control at the same culture condition, the HPLC finger-print of the EtOAc extract of the culture with sodium butyrate (10 µM) in rice medium showed new peaks at about 15, 31, and 38 min ( Figure 1A), and the main peaks of the harziane diterpenoids at 33-42 min ( Figure 1B) disappeared. Chemical investigation of the EtOAc extract led to the isolation of three new terpenoids, including one novel chlorinated cleistanthane diterpenoid, harzianolic acid A (1), one harziane diterpenoid, harzianone E (2), and one cyclonerane sesquiterpenoid, 3,7,11-trihydroxy-cycloneran (3), together with 11 known sesquiterpenoids, including eight cyclonerane sesquiterpenoids, methyl 3,7-dihydroxy-15cycloneranate (4) (Song et al, 2018), catenioblin C (5) (Wu et al, 2012), ascotrichic acid (6) (Xie et al, 2013), cyclonerotriol (7) (Kasitu et al, 1992), (10E)-12-acetoxy-10-cycloneren-3,7-diol (8) (Fang et al, 2018), cyclonerodiol (9) (Nozoe et al, 1970), cyclonerodiol oxide (10) (Fujita et al, 1984) and epicyclonerodiol oxide (11) (Fujita et al, 1984), one african sesquiterpenoid, ophioceric acid (12) (Reátegui et al, 2005), and two acoranetype sesqiuterpenoids, ent-trichoacorenol (13) (Brock and Dickschat, 2011) and trichoacorenol (14) (Huang et al, 1995) (Figure 2). These results revealed that the original main products harziane diterpenoids were replaced by cyclonerane sesquiterpenoids.…”
Section: Chemical Identification Of the Isolated Compoundsmentioning
confidence: 99%
“…Compared to the rice culture control at the same culture condition, the HPLC finger-print of the EtOAc extract of the culture with sodium butyrate (10 µM) in rice medium showed new peaks at about 15, 31, and 38 min ( Figure 1A), and the main peaks of the harziane diterpenoids at 33-42 min ( Figure 1B) disappeared. Chemical investigation of the EtOAc extract led to the isolation of three new terpenoids, including one novel chlorinated cleistanthane diterpenoid, harzianolic acid A (1), one harziane diterpenoid, harzianone E (2), and one cyclonerane sesquiterpenoid, 3,7,11-trihydroxy-cycloneran (3), together with 11 known sesquiterpenoids, including eight cyclonerane sesquiterpenoids, methyl 3,7-dihydroxy-15cycloneranate (4) (Song et al, 2018), catenioblin C (5) (Wu et al, 2012), ascotrichic acid (6) (Xie et al, 2013), cyclonerotriol (7) (Kasitu et al, 1992), (10E)-12-acetoxy-10-cycloneren-3,7-diol (8) (Fang et al, 2018), cyclonerodiol (9) (Nozoe et al, 1970), cyclonerodiol oxide (10) (Fujita et al, 1984) and epicyclonerodiol oxide (11) (Fujita et al, 1984), one african sesquiterpenoid, ophioceric acid (12) (Reátegui et al, 2005), and two acoranetype sesqiuterpenoids, ent-trichoacorenol (13) (Brock and Dickschat, 2011) and trichoacorenol (14) (Huang et al, 1995) (Figure 2). These results revealed that the original main products harziane diterpenoids were replaced by cyclonerane sesquiterpenoids.…”
Section: Chemical Identification Of the Isolated Compoundsmentioning
confidence: 99%
“…Further experiments would be needed to establish the biosynthetic relationship between the two compounds. Catenioblin A has only previously been found in 1 entomopathogenic fungus, Paecilomyces cateniobliquus YMF1.01799 (Wu et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Phomalactone is quite insecticidal (Khambay et al 2000;Wu et al 2012). It has been isolated previously from several species of the fungal genera Nigrospora (Fukushima et al 1998;Trisuwan et al 2009;Wu et al2009), Xylaria (Jimenéz-Romero et al 2008, Aspergillus (Komai et al 2003), Verticillium (Khambay et al 2000), Drechslera (Krivobok et al 1994), Hirsutella (entomopathogenic) ( K r a s n o f f a n d G u p t a 1 9 9 4 ) , P a e c i l o m y c e s (entomopathogenic) (Wu et al 2012), and Phoma (Yamamoto et al 1970).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During our investigation of endophytic fungi from Azadirachta indica, one strain YM311505 was isolated and identified to be Trichoderma longibrachiatum. The study on secondary metabolites of this strain led to the isolation of a new sesquiterpene, named as dihydrocyclonerotriol (1), together with two known compounds, catenioblin C (2) [2] and sohirnone A (3) [3a] (Figure 1). Cyclonerol-related terpenes have been isolated since 1970.…”
mentioning
confidence: 99%